2020
DOI: 10.1186/s13018-020-01748-w
|View full text |Cite
|
Sign up to set email alerts
|

The utility of 18F-FDG PET and PET/CT in the diagnosis and staging of chondrosarcoma: a meta-analysis

Abstract: Objective: Chondrosarcoma is the second most common primary bone sarcoma; however, unlike other tumors, the biopsy cannot easily make a definite diagnosis or predict the histological grade. This meta-analysis was performed to evaluate the utility of 18 F-FDG PET and PET/CT to differentiate chondrosarcoma from benign cartilaginous lesions and to predict the histopathological grade of chondrosarcoma. Material and methods: A comprehensive search was performed in three electronic databases including Medline/ PubMe… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
13
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 31 publications
0
13
0
1
Order By: Relevance
“…The maximum standardized uptake value (SUVmax) seems to correlate with the grade of CHS, and the benign tumors would be rather characterized by lower SUVmax values [ 121 ]. Results published in a recent meta-analysis suggest that FDG PET/CT displays a high specificity and sensitivity in the diagnosis of CHS, superior to scintigraphy; it also seems beneficial for grading and monitoring the tumors [ 118 , 122 ]. However, it was also suggested that the value of SUVmax alone might not be sufficient to differentiate low-grade CHS from benign lesions [ 122 ].…”
Section: Imaging Methods In Chondrosarcomamentioning
confidence: 99%
“…The maximum standardized uptake value (SUVmax) seems to correlate with the grade of CHS, and the benign tumors would be rather characterized by lower SUVmax values [ 121 ]. Results published in a recent meta-analysis suggest that FDG PET/CT displays a high specificity and sensitivity in the diagnosis of CHS, superior to scintigraphy; it also seems beneficial for grading and monitoring the tumors [ 118 , 122 ]. However, it was also suggested that the value of SUVmax alone might not be sufficient to differentiate low-grade CHS from benign lesions [ 122 ].…”
Section: Imaging Methods In Chondrosarcomamentioning
confidence: 99%
“… 26 Analysis is limited to variables provided by the database and may not include demographic or treatment considerations such as patient employment status, hospital size, types of imaging used for staging purposes, or the reported cause of death. Specific to this study, we were not able to determine whether there was utilization of dynamic gadolinium chelate-enhanced MRI and/or PET-CT 10 11 12 13 to obtain and underlying diagnosis. Ultimately, the NCDB is a database, and although there are highly standardized reporting protocols with a number of integrity checks and quality assurance measures to ensure accuracy of reporting, human error and ambiguous diagnoses must be considered in interpretation of results.…”
Section: Discussionmentioning
confidence: 95%
“… 30 Advanced imaging studies continue to improve as dynamic gadolinium chelate-enhanced MRI and/or PET-CT to aid differentiating between cartilaginous tumors. 10 11 12 13 However, if ambiguity remains and a cartilaginous tumor cannot reliably differentiated based on radiographic and advanced imaging with collaboration of a multidisciplinary team, a biopsy is still warranted.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations